Application of Led on Plant Growth Unit in Tomato Cultivation (Bangladesh Journal of Botany, 2021)
Effects of Light Emitting Diode (LED) lamps on plant growth with different modulations on the tomato plant were investigated by applying under actual conditions in the greenhouses. Thus, four different pulse width modulation (PWM) systems from red and blue LEDS at different wavelengths were designed. Trials were performed by using direct current (Mode1), 5Khz-φ = 0o (Mode2), 5Khz-φ = 180o (Mode3) and 1Khz-φ = 0o (Mode4) and the tomato grown under the sun at the same conditions were compared for controlling purposes. Stomata movements and total chlorophyll content of the tomatoes were examined, and the results were compared to the tomatoes that were grown under sun. The custom developed artificial four light source system, a treatment of Mode 2 produced the highest yield, while each treatment played its special role in regulating plant morphology and physiology.Bangladesh J. Bot. 50(3): 523-529, 2021 (September)